Diseño y construcción de sistema lumínico y de suministro de aire comprimido en una pared de burbujas con dimensiones 75 x 60 cm para uso decorativo de la empresa Eventos Revolution (2023)
The purpose of this degree work is to design and build the lighting system with LED technology and compressed air supply in a controlled manner through solenoid valves connected by hoses to cells filled with water generating the effect of bubble wall for decorative use in the events held by the company Eventos Revolution in different spaces such as hotels, offices, bars, restaurants, clubs, farms, among others.